Are children with special risk medical conditions receiving influenza vaccination? Validity of parental and provider report, and to a National Immunisation Register. Issue 4 (3rd April 2019) - Tuckerman, Jane; Crawford, Nigel W; Lynch, John; Marshall, Helen S
ABSTRACT: Background : To investigate the validity of parent reported influenza vaccination and provider reporting to the Australian Immunisation Register (AIR) in children with special risk medical conditions (SRMC). Methods : Cross-sectional survey with parents of children with a SRMC aged ≥ 6 months and <18 years attending the Women's and Children's Hospital, Adelaide, Australia from September 2015 to February 2016. Children aged <7 years provided data to assess provider-AIR reporting. Influenza vaccination status was ascertained from the child's parent, immunisation provider and the AIR. Concordance was made using the Kappa index and the sensitivity, specificity, positive predictive value and negative predictive value were calculated. Results : 389 and 395 parent-provider influenza vaccination records were available for 2014 and 2015 respectively. 78% of parent reported vaccinations were substantiated by a provider with the kappa indicating good (κ = 0.677) to very good agreement (κ = 0.814) for 2014 and 2015 respectively. Discordance was higher in 2014, largely attributable to parents over reporting vaccination. More fathers over reported compared to mothers (Fisher's exact = 0.052). There were 241 provider-AIR influenza vaccination records. Sensitivity of the AIR to reflect a child's influenza immunisation status was low (32.6%). Conclusions : Parental report over estimates confirmed influenza vaccination status and is affected by time and relationship to the child. Only a third of influenza vaccinations were reported to the AIR. Timely accurate data is critical to facilitate vaccination and evaluate program coverage.